Unsaturated Flow Phenomena in Porous Medium as in a Trickling Filter - Ileri, Recep; Muslu, Yilmaz (Wiley, 1996)
The relationship between substrate removal efficiency and dispersion characteristics of biological filters was investigated. Flow measurements were made using tap water and a synthetic feed solution. The importance of changes in fluid regime with regard to the simultaneous transport and reaction within the biological filter was demonstrated. The effect of drop formation and breakage of liquid jets on substrate utilization was shown.